INVESTIGASI MORFOLOGI TWDI (Thin Wall Ductile Iron)AKIBAT PROSES MULTI STAGE SPHEROIDISING - Luchyto Chandra Permadi; Faisol Khoufi Asshidiqi; Dwi Agus Sudjimat (Fakultas Sains dan Teknologi, UNIRA Malang, 2022)
Thin Wall Ductile Iron (TWDI) is used in exhaust manifolds in the automotive industry. TWDI can also be called thin, ductile and strong steel. However, from some of the improvements, further observations are still being made. One of the ways to investigate TWDI is in the form of multi-stage spheroidising heat treatment. He treated this for an in-depth study of preventing the formation of carbides and knowing the structure of TWDI. Temperature and time are the main parameters given to the heat treatment, which is a temperature of 700 0C and held for 30 hours. This is to explore the structure of the surface on. Various empirical evidence shows that it is very important for further observation and development in the improvement of TWDI. Keywords: Investigation, Thin Wall Ductile Iron, Spheroidising